Relasi Antar Tokoh Dalam Novel Selamat Tinggal Karya Tere Liye Sebagai Materi Belajar Unsur Intrinsik Novel Ditingkat SMA Kelas XII - Diar Indah Irwanasari; Nazla Maharani U; Pipit Mugi Handayani (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The background of this research is the novel Selamat Selamat, written by Tere Liye, which is very focused on the course of an interrupted study period. Apart from problems in the world of education, there is the development of talent that has been hidden for a long time and is re-emerging because someone makes the story in the novel even more interesting to read until the end because the story line is very good, and the novel can be linked to intrinsic learning material in high school. The approach in this research is descriptive qualitative. The data source is the text of the novel Selamat Selamat by Tere Liye. The form of data is in the form of written data, namely, character quotes from the characters in the novel Selamat Selamat By Tere Liye as an alternative learning material for intrinsic elements in high school. Data collection techniques use documentation techniques. The data analysis technique uses descriptive analysis and the technique for presenting the results of data analysis is carried out descriptively. The results of the analysis of Tere Liye's novel Selamat Selamat, which has been carried out and can be seen, is that the novel Selamat Selamat By Tere Liye has a form that can be analyzed in the form of character traits, conversational relationships between one character and another, story setting, theme and message. Social relationships between characters which contain conversations that occur between one character and another character. In the intrinsic element, there is characterization, there are characters from the characters in the novel Selamat Selamat by Tere Liye. Next there is a theme, namely about education and in the background there is a place, time and socio-cultural setting.